OPTIMASI PERTUMBUHAN BIBIT ANGGREK Dendrobium Sp. STADIA REMAJA DENGAN PEMBERIAN GROW QUICK LB - SIRLYANA SIRLYANA; SURTINAH SURTINAH (Jurnal Ilmiah Pertanian, 2019)
The purpose of the research was to obtain concentration Grow Quick LB optimum for growth of seedlings of Orchid Dendrobium Sp.Environmental design used was complete Random Design. The design of the treatment given is concentration Grow Quick LB 0 cc l-1 water, 0.5 cc l-1 water, 1cc l-1 water, 1.5 l -1water, 2 ccl-1 water, and 2.5 cc l-1 water.The data obtained were analyzed using polynomial regression. The research results obtained that the higher seed, and number of leaves of Dendrobium orchids with optimum pemberianGrow Quick 1.5 LB cc l-1. of water.Optimum leaf length is obtained by the giving Grow Quick LB with a concentration of 0.3 cc l-1 of water.The width of the leaves and shoots of the optimum amount is obtained by granting the Grow Quick LB with a concentration of 0.2 cc l-1 of water.